2009
DOI: 10.1108/14635780910972288
|View full text |Cite
|
Sign up to set email alerts
|

What determines the capital structure of real estate companies?

Abstract: Purpose -This paper aims to investigate the determinants affecting the choice of the capital structure of European property companies. Design/methodology/approach -The analysis considers the set of companies belonging to the EPRA/NAREIT Europe Index (both REITs and non-REITs) and is based on panel data to get greater reliability and to check the cross-time path of explanatory variables. Seven independent variables (size, profitability, growth opportunities, cost of debt, ownership structure, risk, and category… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 84 publications
4
29
1
Order By: Relevance
“…In their study, the profitability and operating risk were found negatively correlated with leverage ratio, while tangibility and growth rate was positive correlated. Morri and Cristanziani (2009) examined both REITs and non-REITs companies in European countries. Their findings confirmed the importance of the tax-exempt status for REITs in capital structure choices.…”
Section: Literature Of Property Firms' Financial Behaviourmentioning
confidence: 99%
“…In their study, the profitability and operating risk were found negatively correlated with leverage ratio, while tangibility and growth rate was positive correlated. Morri and Cristanziani (2009) examined both REITs and non-REITs companies in European countries. Their findings confirmed the importance of the tax-exempt status for REITs in capital structure choices.…”
Section: Literature Of Property Firms' Financial Behaviourmentioning
confidence: 99%
“…Morri andCristanziani (2009), ooi (1999), and Mallikarjunappa and Goveas (2007) show insignificant relationship between growth and leverage. However, empirical studies have mixed results of the growth and leverage, for example, Gwatidzo and Ramjee (2012), Ameer (2013) and Bayrakdaroglu et al (2013) find a positive relation between growth and leverage while abbad and zaluki (2012), Gurcharan (2010) and Antoniou et al (2008) show negative association between growth and leverage.…”
Section: Growthmentioning
confidence: 99%
“…Contextually, to calculate these parameters, other information must be inserted into the data regarding the financial leverage ratio of companies in the real estate development sector [79,80]. From this ratio it has been possible to obtain the leverage degree that transport it directly to the WACC formula; the degree of financial leverage is given by the expression: NAF = D/(E + D), therefore: E/(E + D) + NAF = 1.…”
Section: The Level Of Financial Leverage: Determination Of E and Dmentioning
confidence: 99%